PELAKSANAAN TANGGUNG JAWAB BANQUET CAPTAIN PADA DEPARTMEN F&B DI HOTEL NOVOTEL PEKANBARU - Wijaya, Fredy Lea; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hotels include business ventures that put pressure on sales of services. One of the activities carried out by the company to achieve sales targets is to implement good and efficient operational implementation to consumers. Without implementing this kind of effort to increase sales of function rooms is very difficult because there is a lot of competition that is happening right now. This study aims to determine how the implementation of the responsibilities of the Novotel Pekanbaru captain banquet. This study using qualitative method with descriptive approach in which the researcher will retrieve data from informants to find out the issues raised regarding the implementation of the banquet captain responsibilities of the Novotel Hotel in Pekanbaru. While collecting the datas, this study use observation, interviews, and documentation. From the results of the research the indicators are giving assignments, bill banquet, making side jobs, break up schedules, arranging meal schedules, giving special jobs, briefings, determining prayer schedules, designating over time, handling guests, appointing assignments to store banquet, and provide input. The results showed that the captain's banquet carried out the task in according to the responsibilities. In carrying out the banquet captain duties there are several obstacles, such a miss communication with sales and marketing, and the lack of employees in the banquet section. Keywords: implementation, banquet captain, food and beverage department